The Effect of Upward Comparison on Body Dissatisfaction Among Female Patients in Aesthetic Clinics - Muhammad Nur Hidayat Nurdin; Kurniati Zainuddin; Yusfitri Nursyahwalni Mangarengi; Zahir Alfattah Darussalam (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Abstract This study aims to examine the effect of upward comparison on body dissatisfaction among female patients at aesthetic clinics. The research employed a quantitative correlational method with a population consisting of female aesthetic clinic patients. The sample included 150 women aged 18–25 years, selected using an incidental sampling technique. Data were collected through the adapted versions of The Upward and Downward Appearance Comparison Scale (UDACS) and the Multidimensional Body-Self Relations Questionnaire–Appearance Scale (MBSRQ-AS). The collected data were analyzed using a simple linear regression test. The results revealed a significant effect of upward comparison on body dissatisfaction among female aesthetic clinic patients. Furthermore, the findings showed a positive direction of influence, with an effective contribution of 19.6%. This indicates that the higher the level of upward comparison, the higher the level of body dissatisfaction.